Rancang Bangun Chatbot Pedoman Penulisan Karya Tulis Ilmiah Universitas Nias Berbasis Web Menggunakan Metode Keyword Matching - Enjellyn Sarumaha; Clara Ester Nikmat Gulo; Ifolala Natafati Ziliwu; Jurisman Waruwu (CV. SINAR HOWUHOWU, 2026)
This research aims to develop a web-based chatbot application as an interactive information medium for the Scientific Paper Writing Guidelines at Universitas Nias. Student often face diffiuclties and require a long time to find specific regulations within thick guidelines documents. To solve this issue, a chatbot system was developed using the Keyword Matching method. This method works by matching the keywords input by users with the data pattern stored in the database to provide relevant answers. System development was carried out using the Waterfall model, including requirements analysis, system design with UML (Use Case and Activity Diagrams), implementation using PHP and MySQL, and testing. The result of this research is a responsive web-based chatbot application capable of providing fast and precise information regarding formatting, structure, and academic writing regulations. In conclusion, the implementation of this chatbot effectively improves the accessibility and efficiency of services related to scientific writing guidelines for the academic community of Universitas Nias.